DETERMINAN DISIPLIN KERJA KARYAWAN - I Komang Trisna Eka Putra (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
This study aimed to determine: to analyze the determinants of employee work discipline. This study took place at PT. Summit Oto Finance Denpasar Branch involving 35 respondents. This type of research is quantitative descriptive analysis. Indicators of employee work discipline that are used are work time discipline, carrying out leadership instructions, job success, adherence to work rules and procedures. The results of this study prove that work time discipline, carrying out leadership instructions, work success, adherence to regulations and work procedures significantly have a positive effect on employee work discipline and high work discipline will improve employee performance. The lower value of indicators of employee job success due to there are several factors such as: accuracy in work, and reward.